RELATIONSHIP OBESITY WITH THE MENSTRUAL CYCLE ON STUDENTS SMAN 2 BANDAR LAMPUNG - Rehana, Intan; Berawi, Khairunnisa; -, Susianti; -, Muhartono (Majority, 2015)
Abstract One of the typical maturity of a woman is menstruating. However, the variation of the menstrual cycle and menstrual disorders often occur. Irregular menstrual cycles have implications for women’s health. There are many things that affect the menstrual cycle, including nutritional status. Women who are obese are more prone to disruption the menstrual cycle due to the influence of Adypocyte -derived hormone leptin from body fat. This type of analytic research with cross sectional approach that aims to the relationship of obesity with the menstrual cycle. The number of samples in this study amounted to 107 people with a sampling technique with simple random sampling method. Data on menstrual cycle obtained from interviews while body mass index obtained from direct measurements. The result showed that the average weight of the sample was 57.42 kg with a mean height of the sample was equal to 158.40 cm, while the mean body mass index of the sample was equal to 22.40. Fischer test results obtained significant association between obesity and the menstrual cycle in students SMA N 2 Bandar Lampung with p = 0.032 ( p < 0.05 ). Key word: Leptin, menstrual cycle, nutritional status, obesity. Abstrak Salah satu ciri khas kedewasaan seorang perempuan adalah menstruasi. Namun, variasi dari siklus menstruasi dan gangguan menstruasi sering terjadi. Siklus menstruasi yang tidak teratur ini berimplikasi terhadap kesehatan wanita. Ada banyak hal yang mempengaruhi siklus menstruasi, diantaranya status gizi. Wanita yang obesitas akan lebih mudah mengalami gangguan siklus mentruasi akibat pengaruh Adypocytederived hormone Leptin yang berasal dari lemak tubuh. Jenis penelitian ini berupa analitik dengan pendekatan belah lintang yang bertujuan untuk untuk hubungan obesitas dengan siklus menstruasi. Jumlah sampel dalam penelitian ini berjumlah 107 orang dengan tekhnik pengambilan sampling dengan metode simple random sampling. Data mengenai siklus menstruasi didapatkan dari wawancara sedangkan indeks massa tubuh didapatkan dari pengukuran langsung. Dari hasil penelitian didapatkan bahwa rerata berat badan sampel adalah sebesar 57,42 kg dengan rerata tinggi badan sampel adalah sebesar 158,40 cm sedangkan rerata indeks massa tubuh sampel adalah sebesar 22,40. Hasil uji Fischer didapatkan hubungan bermakna antara obesitas dengan siklus menstruasi pada siswi SMA N 2 Bandar Lampung dengan p= 0,032 (p<0,05). Kata kunci : Leptin, obesitas, status gizi, siklus menstuasi